Static and Dynamic Analyses of a Long-Span Cable-Stayed Bridge with Corroded Cables - Xiang, Yang (Université d'Ottawa / University of Ottawa, 2018)
This study investigates the static behavior and dynamic behavior of the Stonecutters Cable-Stayed Bridge, which is the third longest cable-stayed bridge in the world, when a group of 8 cables is damaged by corrosion. In this thesis, the reduction in cable cross-section area is used to simulate the corrosion level. The corroded cables are divided into 2 groups of 4 cables, arranged in symmetric and asymmetric distributions on both decks. A finite element bridge model was employed to perform the analysis. The validation of the model was established by comparing numerical results to the published results of the bridge. The model was then subjected to gravity load only to check the effects of corrosion level, the distance of the corroded cables and the distribution of the damaged cables on the decks’ deflection and cable stresses change. In the dynamic analysis, the natural frequencies and mode shapes were compared with a reference case with no corrosion-damaged cables. A recorded wind load was applied on the deck to investigate the time-history response of the mid-span in the horizontal, vertical and torsional directions, and of the tower top in the horizontal direction. Moreover, frequency analysis was performed on the time-history response, and coupled motions at certain frequencies were observed. Numerical results as the ones presented in this thesis can complement information gathered from non-destructive testing technology in detecting corrosion-damaged stay-cables in cable-stayed bridges.
Keywords: long-span cable-stayed bridge; corroded cables; static analysis; dynamic analysis